2007
DOI: 10.1099/ijs.0.64690-0
|View full text |Cite
|
Sign up to set email alerts
|

Haloquadratum walsbyi gen. nov., sp. nov., the square haloarchaeon of Walsby, isolated from saltern crystallizers in Australia and Spain

Abstract: Strains C23T and HBSQ001 were isolated from solar salterns and are novel square-shaped, aerobic, extremely halophilic members of the domain Archaea and family Halobacteriaceae. Cells stained Gram-negative and grew optimally in media containing 18 % salts at around neutral pH. Mg2+ is not required. The DNA G+C content of both isolates was 46.9 mol% and DNA–DNA cross-hybridization showed a relatedness of 80 %. Their 16S rRNA gene sequences showed only 2 nucleotide differences (99.9 % identity) and phylogenetic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
157
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(163 citation statements)
references
References 27 publications
3
157
1
2
Order By: Relevance
“…The minimal standards for the description of new taxa within the order Halobacteriales were followed (Oren et al, 1997), using previously described methods (Burns et al, 2007;Gutierrez et al, 2002;Torreblanca et al, 1986). For growth/activity tests, cells were inoculated into characterization medium CM (Burns et al, 2007), with or without the addition of a specific nutrient.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The minimal standards for the description of new taxa within the order Halobacteriales were followed (Oren et al, 1997), using previously described methods (Burns et al, 2007;Gutierrez et al, 2002;Torreblanca et al, 1986). For growth/activity tests, cells were inoculated into characterization medium CM (Burns et al, 2007), with or without the addition of a specific nutrient.…”
mentioning
confidence: 99%
“…For growth/activity tests, cells were inoculated into characterization medium CM (Burns et al, 2007), with or without the addition of a specific nutrient. Reference strains included Haloferax volcanii NCIMB 2012 T , Halogeometricum borinquense JCM 10706 T , Haloterrigena turkmenica JCM 9101 T , Halomicrobium mukohataei JCM 9738 T and Halobiforma haloterrestris JCM 11627 T .…”
mentioning
confidence: 99%
“…Recently, the extent of the family has been undergoing rapid expansion, with the description (as of June 2007) of five new genera and 20 novel species since 2006. This expansion has been due not only to the identification of novel taxa isolated from well-known hypersaline environments, such as the genera Halovivax, Halostagnicola, Haloplanus and Haloquadratum (Castillo et al, 2006a, b;Bardavid et al, 2007;Burns et al, 2007), but also to the recognition that members of the Halobacteriales can grow within saline microniches in non-saline environments at relatively low salt concentrations (Elshahed et al, 2004a;Savage et al, 2007). In addition, recent studies have reported the isolation of novel halobacterial strains (Purdy et al, 2004;Fukushima et al, 2007) or the detection of novel Halobacteriales-affiliated 16S rRNA gene sequences from moderate-to low-salinity systems (Munson et al, 1997;Takai et al, 2001;Walsh et al, 2005).…”
mentioning
confidence: 99%
“…Differential characteristics between strain BZ256 T and closely related genera within the order Halobacteriales Taxa: 1, strain BZ256 T ; 2, Halogeometricum; 3, Halobaculum; 4, Haloquadratum; 5, Halorubrum; 6, Haloferax; 7, Halococcus. Data for reference genera are from Burns et al (2007), Castillo et al (2006c), Cui et al (2006), Goh et al (2006), Grant et al (2001), Montalvo-Rodriguez et al (1998), Oren et al (1995) and Xu et al (2007). +, Positive; 2, negative; +/2, variable; NR, not reported.…”
mentioning
confidence: 99%
“…Extremely halophilic archaea, members of the Halobacteriaceae, have been isolated from various hypersaline environments and are classified into 26 genera (Tindall et al, 1984;Torreblanca et al, 1986;McGenity & Grant, 1995;Oren et al, 1995Oren et al, , 2002Kamekura & Dyall-Smith, 1995;Kamekura et al, 1997;McGenity et al, 1998;Montalvo-Rodriguez et al, 1998;Ventosa et al, 1999;Xu et al, 1999;Wainø et al, 2000;Grant, 2001a, b;Hezayen et al, 2002;Vreeland et al, 2002, Itoh et al, 2005Xue et al, 2005;Castillo et al, 2006a, b;Savage et al, 2007;Burns et al, 2007;Bardavid et al, 2007;Gutiérrez et al, 2007). The genus Haloterrigena was established by Ventosa et al (1999) to accommodate the species Haloterrigena turkmenica (formerly Halococcus turkmenicus).…”
mentioning
confidence: 99%